2023
DOI: 10.3390/microorganisms11041033
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Antimicrobial Resistance Trends in Commensal Escherichia coli Isolated from Cecal Samples of Swine at Slaughter in the United States, 2013–2019

Abstract: The emergence of antimicrobial resistance (AMR) in commensal and pathogenic enteric bacteria of swine is a public health threat. This study evaluated publicly available AMR surveillance data collected by the National Antimicrobial Resistance Monitoring System (NARMS) by assessing AMR patterns and temporal trends in commensal E. coli isolated from cecal samples of swine at slaughter across the United States. We applied the Mann-Kendall test (MKT) and a linear regression trend line to detect significant trends i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…Our research shows that there was no significant change in the likelihood of detecting tetracycline-resistant Salmonella and Escherichia in ground beef and pork chops after the VFD rule changes were implemented in 2017, compared to before the changes. Our study’s results align with recent research that found no significant change in the prevalence of tetracycline-resistant Escherichia in cecal samples of swine at slaughter in the U.S. between 2013 and 2019 [ 75 ]. There is no systematic collection of medically important antibiotic consumption data at the farm-level in the U.S. [ 71 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our research shows that there was no significant change in the likelihood of detecting tetracycline-resistant Salmonella and Escherichia in ground beef and pork chops after the VFD rule changes were implemented in 2017, compared to before the changes. Our study’s results align with recent research that found no significant change in the prevalence of tetracycline-resistant Escherichia in cecal samples of swine at slaughter in the U.S. between 2013 and 2019 [ 75 ]. There is no systematic collection of medically important antibiotic consumption data at the farm-level in the U.S. [ 71 ].…”
Section: Discussionsupporting
confidence: 91%
“…It should be noted that, while streptomycin, an aminoglycoside, is not included in the EFSA and ECDC testing panel, relatively high levels of resistance are expected, in line with cross-sectional European studies [63][64][65][66][67]. High levels of streptomycin resistance, not evaluated in the most recent NARMS data but included previously [68], are also reported in the USA [58]. Table 2 summarises the results from a selection of studies that investigated AMR in commensal E. coli isolated from healthy finisher pigs on farm or at slaughter.…”
Section: Resistance In Escherichia Coli Isolated From Finisher Pigs: ...mentioning
confidence: 61%
“…Several European states also operate their own monitoring programmes, for example, the Danish Integrated Antimicrobial Resistance Monitoring and Research Programme (DANMAP) in Denmark [54] and the Monitoring of Antimicrobial Resistance and Antibiotic Usage in Animals in the Netherlands (MARAN) programme in the Netherlands [55]. As these monitoring programmes mature, more detailed analyses, e.g., of multiyear trends, will become available, as is the case for Portugal, Denmark, and the USA [56][57][58]. Schrijver et al (2018) reviewed the monitoring programmes in operation in Europe up until 2016 and found marked heterogeneity in sampling and laboratory methodology, as well as in the availability of results (i.e., language and frequency of publication) [59].…”
Section: Antimicrobial Resistance In Escherichia Coli Of Porcine Orig...mentioning
confidence: 99%
“…This explains the high resistance levels to these antibiotics on broiler farms. Moreover, a study conducted between 2013 and 2019 revealed that the resistance and multiresistance of E. coli strains to important antibiotics for human medicine, such as third-generation cephalosporins and meropenem, have increased over time compared to 2013 [31]. This trend of antibiotic resistance is concerning.…”
Section: Discussionmentioning
confidence: 99%